Smartlock using fingerprint sensor / Ahmad Mustaqim Abdu Rahim ... [et al.] - Abdu Rahim, Ahmad Mustaqim; Mohd Faisol, Muhammad Adlan; Nor Azha, Nur Alia Ezanie; Khusair, Muhammad Khairul Fikri; Mustafa, Aisamuddin Aizat; Thominathan, Santhanamery (2020)
Padlocks are being an essential part in our daily lives. It is used to save guard our properties especially when we are away. However, we often hear that the robbery rates in our community are in the increase although we carefully lock our properties using the padlocks. This is due to the weaknesses of our current padlocks that can be easily tampered and broken to gain access to our properties. As such are more secured and reliable padlocks are needed to protect our properties. Therefore, The Smartlock Using Fingerprint Sensor is designed and developed using the latest technology into the padlock. It uses fingerprint sensors for unlocking systems and also an alert system for the safety measures. The alarm system embedded in the padlock will be active and produce a high pitch sound when someone unauthorized attempted to unlock the padlock. This means that the possibility of the lock being broken will be minimized and security of our belongings will be upheld. A mini sized microcontroller is installed in to the padlocks which can save up to 10 different fingerprints in a single padlock which will be convenient for the household that has multiple numbers of family members or occupants.